AN ANALYSIS OF INFLECTIONAL MORPHOLOGY USED IN STUDENTS’ WRITING - Febriyanti; Eva Nurchurifiani; Sri Wahyuningsih (JETA (Journal of English Teaching and Applied Linguistic), 2021)
The study aimes to analyse inflectional morphology used in students’ writing. It is qualitative study. There were 73 students the fourth semester of English department of STKIP PGRI Bandar Lampung who were taken purpossively as the sample. It is found that, from 554 sentences, there are 17.15% (or 95 words) errors made by the students in the forms of nouns, 19.13% (or 106 words) errors in the forms of pronouns and determiners, 96.2% (or 533 words) errors in the forms of verbs, and 2.53% (or 14 words) errorrs in the forms of adjectives. Based on the results, it is known that the EFL learners mostly made errors in using verbs in the term of infectional mophology.